Probiotic infant cereal improves children's gut microbiota: Insights using the Simulator of Human Intestinal Microbial Ecosystem (SHIME®) - Salgaço, Mateus Kawata [UNESP]; Perina, Natália Partis; Tomé, Thaís Moreno; Mosquera, Elaine Martins Bento; Lazarini, Tamara; Sartoratto, Adilson; Sivieri, Katia [UNESP] (Elsevier, 2021)
Infant́s gut microbiota can be modulated by many factors, including mode of delivery, feeding regime, maternal diet/weight and probiotic and prebiotic consumption. The gut microbiota in dysbiosis has been associated with innumerous diseases. In this sense, early childhood intestinal microbiome modulation can be a strategy for disease prevention. This study had the purpose to evaluate the effect of an infant cereal with probiotic (Bifidobacterium animalis ssp. lactis BB-12®) on infant́s intestinal microbiota using SHIME®, which simulates human gastrointestinal conditions. The ascending colon was inoculated with fecal microbiota from three children (2–3 years old). NH4+, short chain fatty acids (SCFASs) and microbiota composition were determined by selective ion electrode, GC/MS and 16S sequencing, respectively. After treatment, butyric acid production increased (p < 0.05) 52% and a decrease in NH4+ production was observed (p < 0.01). The treatment stimulated an increase (p < 0.01) of Lactobacillaceae families, more precisely L. gasseri and L. kefiri. L. gasseri has been associated with the prevention of allergic rhinitis in children and L. kefiri in the prevention of obesity. Thus, infant cereal with BB-12® is able to stimulate the growth of L. gasseri and L. kefiri in a beneficial way, reducing NH4+ and increasing the production of SCFAs, especially butyric acid, in SHIME®.
Keywords: Bifidobacterium lactis; Infant cereal; Intestinal metabolites; Microbiota; SCFAs; SHIME® model